Determination of Competitiveness : Price and Promotion (Marketing Management Literature Review) - Kania Rifdah Gunawan; Reni Silviah (Siber Nusantara Review, 2024)
Literature Review of Price Determination, and Promotion in Increasing Competitiveness is a scientific article with the aim of analyzing whether products, prices, and promotions play a role in Competitiveness. The qualitative approach method with the literature review method to explore and analyze the relationship between price, promotion, and competitiveness. The results of this article are: 1) Price plays a role in increasing Competitiveness, 2) Promotion plays a role in increasing Competitiveness. Apart from these 2 exogenous variables that affect the endogenous variable of Competitiveness, there are still many other factors including social media, viral marketing, and place atmosphere.